Buying and Selling Tickets Without Seat Numbers Through the Access By KAI Application: An Islamic Legal Perspective - Siti Salsabila (al-Afkar, Journal For Islamic Studies, 2025)
Islamic law is a sharia, which is a set of rules established by Allah SWT for His followers through the Prophet Muhammad SAW.These rules encompass laws related to beliefs (aqidah) as well as those governing the behavior (amaliyah) of Muslims.In general, the scope of Islamic law is very broad, not only regulating matters of worship (ḥabl min Allāh), but also governing aspects of muamalah, which are the relationships among fellow humans (ḥabl min an-nās).Muamalah encompasses all religious provisions that regulate interactions among humans, including the relationship between humans and their lives as well as their surrounding environment.Allah SWT has decreed that every individual certainly needs others, helps each other, and exchanges needs in various aspects of life, whether through buying and selling transactions, renting, cooperation, or partnerships.In practice, buying and selling tickets through the Access by KAI app is actually similar to other ticket purchasing apps.Through this application, passengers can easily purchase tickets by entering their personal information, selecting the available payment method, and then receiving a ticket or barcode as a boarding pass issued by the application.In addition to facilitating ticket purchases and seat selection, the Access by KAI app also provides an option for tickets without seat facilities marked as "Available (Without Seat)."This means that passengers purchase tickets without a guaranteed seat number.Thus, even though the ticket prices are the same, the facilities received are different.This situation results in passengers who buy tickets without seat numbers not getting a seat.Passengers then occupy empty seats if available, but if all seats are fully occupied, they are forced to stand.It is necessary to examine the Islamic legal perspective on the ticket sales transaction without seat numbers through the Access by KAI application, whether in practice the contract used in the application has fulfilled all the pillars and conditions of sale stipulated by Islamic law.